Hybrid reactive power compensator with adaptation of the operation of the control system to the parameters of the mains voltage - Goolak, S.; Tkachenko, V.; Kyrychenko, M.; Kozlov, S. (Institute of Power Engineering, 2023)
The aim of the work is to develop a model of a hybrid reactive power compensator with adaptation of the control system to the parameters of the voltage supply. The task was achieved by applying the control algorithm for the operation of the control system of the active part of the reactive power compensator, which is based on the regression analysis method. The traction drive of the AC electric locomotive VL-80K, which is operated on the railways of the Ukraine, was chosen as the object of study. The simulation of the traction drive operation was carried out for a traction drive with and without a reactive power compensator, for cases where the process of changing the voltage in the catenary was a stationary deterministic process and for the case when this process was a non-stationary non-deterministic process. The most important result is the development of a block diagram of the control system for the active part of the reactive power compensator based on the implementation of the Levinson-Durbin linear prediction algorithm. The significance of the results obtained lies in the possibility of the proposed control scheme for the active part of the compensator to adapt the operation of the compensator to the voltage parameters of the catenary, that is, to the actual operating conditions of the electric locomotive.
Keywords: active power; reactive power; apparent power; reactive power compensation; traction drive; electric locomotive; control system